Two-year clinical outcomes of the "Italian diffuse/multivessel disease absorb prospective registry" (IT-DISAPPEARS). (1st September 2019) - De Carlo, Marco; Testa, Luca; Leoncini, Massimo; Nicolini, Elisa; Varbella, Ferdinando; Cortese, Bernardo; Ribichini, Flavio; Bartorelli, Antonio L.; Calabria, Paolo; Indolfi, Ciro; Tomai, Fabrizio; Loi, Bruno; et al.
Abstract: Background: Large prospective studies on the use of bioresorbable vascular scaffolds (BVS) for diffuse coronary artery disease are lacking. IT DISAPPEARS is a large multicentre prospective registry investigating the short and long-term outcomes of everolimus-eluting BVS in patients with long coronary lesions and/or multivessel coronary artery disease (ClinicalTrials.gov :NCT02004730 ). We hereby report the 2-year outcomes of the registry. Methods: We enrolled 1002 patients with complex lesions undergoing implantation of 2040 BVS with a prespecified technique including predilation, correct sizing, and postdilation with non-compliant balloons. The primary endpoint was the rate of device-oriented composite endpoint (DOCE), consisting of cardiac death, target vessel-related myocardial infarction (MI), and ischaemia-driven target lesion revascularization (TLR). Secondary endpoints included: 1) patient-oriented composite endpoint (POCE), consisting of all-cause mortality, all infarctions and all revascularisations; 2) definite/probable scaffold thrombosis. Results: Clinical presentation was an acute coronary syndrome in 59.8% of patients. Total BVS length implanted was 47 ± 22 mm. Postdilation of all scaffolds per patient was performed in 96.8%, while optimal implantation as per study guidelines was applied in 71.4%. Through 2-year follow-up, DOCE occurred in 9.5% of patients (cardiac death 0.6%, target vessel-related MI 5.3%, TLR 6.6%). The rate of POCE was 16.6% and of scaffold thrombosis 1.1%. Female gender, total length of coronary lesions, treatment of bifurcation lesions and use of 2.5 mm scaffolds were independent predictors of DOCE. Conclusions: The 2-year results of IT-DISAPPEARS show that BVS may yield acceptable clinical outcomes in patients with complex coronary lesions when the implantation technique is appropriate. Highlights: Diffuse coronary disease should maximise the advantages of bioresorbable scaffolds. We present the largest prospective registry dedicated to this patient subset. We recommended routine lesion predilation and scaffold postdilation. The 2-year clinical outcomes were acceptably good. Very low scaffold thrombosis rates between 1 and 2 years of follow-up.